2020
DOI: 10.1136/annrheumdis-2020-eular.1955
|View full text |Cite
|
Sign up to set email alerts
|

Op0019 stable Versus Tapered and Withdrawn Treatment With Tumor Necrosis Factor Inhibitor in Rheumatoid Arthritis Remission (Arctic Rewind): A Randomised, Open-Label, Phase 4, Non-Inferiority Trial

Abstract: Background:Remission is the preferred treatment target in rheumatoid arthritis (RA), and many patients require biologic DMARDs to reach this state. It is debated whether tapering of tumor necrosis factor inhibitor (TNFi) treatment to discontinuation should be considered in RA patients who sustain remission on treatment (1).Objectives:The primary study objective was to assess the effect of tapering and withdrawal of TNFi on the risk of flares in RA patients in clinical remission.Methods:In the non-inferiority A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Non-inferiority was not demonstrated as 37.2% (tapering/stopping) vs 95.1% (continuation) maintained DAS44 remission (risk difference: 58% (95% CI 43% to 74%)) after 1 year. In the tapering arm 19% of patients experienced radiographic progression of joint damage, compared with 10% in the TNFi continuation arm 50…”
Section: Resultsmentioning
confidence: 97%
“…Non-inferiority was not demonstrated as 37.2% (tapering/stopping) vs 95.1% (continuation) maintained DAS44 remission (risk difference: 58% (95% CI 43% to 74%)) after 1 year. In the tapering arm 19% of patients experienced radiographic progression of joint damage, compared with 10% in the TNFi continuation arm 50…”
Section: Resultsmentioning
confidence: 97%
“…Finally, regarding safety, to our knowledge, this is the first study showing potentially fewer severe adverse events in the spacing versus maintenance arms in terms of infectious events. [14][15][16][17][18][19][20][21][22] Actually, the common thinking for safety issues is a phenomenon called "depletion of the susceptible," whereby people at risk of the most common treatment side effects are likely to experience them in the first months after treatment initiation; consequently, patients with adequate and durable responses to the treatment are those with low risk profile. 34 Our findings indicate that, as shown in many other chronic diseases, drug tapering can lead to disease reactivation, including severe flares and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, our results agree with current knowledge on bDMARD discontinuation strategy. Trials assessing a disease activity–driven tapering strategy for TNFi treatment, such as STRASS or ARCTIC REWIND, did not demonstrate NI in terms of flare occurrence: flares occurred in 76.6% and 63% of patients tapering the TNFi, respectively, versus 46.5% and 5% of patients maintaining bDMARDs at a full dose 17,19 . Only the DRESS trial demonstrated NI of tapering compared to maintenance strategy for major flares but not short‐term flares 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations